2020
DOI: 10.1371/journal.ppat.1009134
|View full text |Cite
|
Sign up to set email alerts
|

The SUMOylation pathway suppresses arbovirus replication in Aedes aegypti cells

Abstract: Mosquitoes are responsible for the transmission of many clinically important arboviruses that cause significant levels of annual mortality and socioeconomic health burden worldwide. Deciphering the mechanisms by which mosquitoes modulate arbovirus infection is crucial to understand how viral-host interactions promote vector transmission and human disease. SUMOylation is a post-translational modification that leads to the covalent attachment of the Small Ubiquitin-like MOdifier (SUMO) protein to host factors, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 84 publications
(129 reference statements)
0
18
0
Order By: Relevance
“…As with other viruses, modulation of SUMOylation is nontrivial and likely time-dependent; depletion of the only E2 for SUMO, UBC9, protects against CHIKV infection in mice, [94] yet depletion of SUMOylation enhances SFV replication in mosquito cells. [95] Cleavage of UBE2Q1 in muscle may disrupt B4GALT1mediated cell adhesion to laminin and promote myoblast and satellite cell differentiation and syncytia formation [96,97] to allow infection of myofibers without virion egress. [98][99][100] This is supported by the ability of alphaviruses to form filopodia-like protrusions mediating cell-to-cell transmission [101] and possibly to shield the virus from antibodies, making effective vaccination more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…As with other viruses, modulation of SUMOylation is nontrivial and likely time-dependent; depletion of the only E2 for SUMO, UBC9, protects against CHIKV infection in mice, [94] yet depletion of SUMOylation enhances SFV replication in mosquito cells. [95] Cleavage of UBE2Q1 in muscle may disrupt B4GALT1mediated cell adhesion to laminin and promote myoblast and satellite cell differentiation and syncytia formation [96,97] to allow infection of myofibers without virion egress. [98][99][100] This is supported by the ability of alphaviruses to form filopodia-like protrusions mediating cell-to-cell transmission [101] and possibly to shield the virus from antibodies, making effective vaccination more difficult.…”
Section: Discussionmentioning
confidence: 99%
“…SUMO modification is known to be well-conserved between species; including H. sapiens, D. melanogaster , and S. cerevisiae ( Epps and Tanda, 1998 ; Fraser et al, 2000 ; Apionishev et al, 2001 ; Hayashi et al, 2002 ; Urena et al, 2016 ; Li et al, 2021 ). Bioinformatic analysis of the amino acid sequence and tertiary structure of SUMO proteins, E2 conjugating enzyme (Ubc9), and SUMOylation activating heterodimer (SAE1/2) has demonstrated these high conservation rates ( Stokes et al, 2020 ; Li et al, 2021 ). Interestingly, while previous studies show most eukaryotic organisms express both a SUMO1 and SUMO2/3 paralog, insects do not possess a SUMO1 paralog, and the insect SUMO2/3 paralogs lack the SCM ( Choy et al, 2013 ; Urena et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…During infection and replication, viruses manipulate the SUMOylation process to ensure viral persistence within the host ( Varadaraj et al, 2014 ; Wimmer and Schreiner, 2015 ; Loboda et al, 2019 ; El Motiam et al, 2020 ). Multiple depletion studies have implicated components of the SUMOylation pathway in viral survival, pathogenesis, and host immunity ( Chiu et al, 2007 ; Brown et al, 2016 ; Conn et al, 2016 ; Su et al, 2016 ; Guo et al, 2017 ; Feng et al, 2018 ; Zhu et al, 2019 ; Stokes et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Aedes aegypti Aa20 and Aag2 cells showed that RNASEK knockdown resulted in reduced DENV replication providing further evidence of its unique role in virus infection [59]. Furthermore, three essential genes (SUMO-activating enzyme E1, SUMO-conjugating enzyme UBC9, and E3 SUMO-protein ligase) of the SUMOylation pathway, known to play a key role in the regulation of host anti-viral defence against arbovirus infection such as Zika virus (ZIKV), Semliki Forest virus, and Bunyamwera virus in mosquito cells, were significantly up-regulated at 6 hpi [60].…”
mentioning
confidence: 85%